Genomic and Transcriptomic Differentiation of Independent Invasions of the Pacific Oyster Crassostrea gigas - Wegner, K. Mathias; Lokmer, Ana; John, Uwe (Frontiers in Ecology and Evolution, 2020)
Upon colonizing new habitats, invasive species face a series of new selection pressures as a result of changing abiotic conditions and novel biotic interactions with native species. These new selection pressures can be accommodated by different mechanisms that act on different levels and across different time scales: 1) By changing transcriptomic profiles, species can react by plasticity within individual physiological limitations. 2) Invasive populations can adapt by fixing beneficial genetic variants in response to the newly encountered selection pressures. Here, we compare the genomic and transcriptomic landscapes of two independent invasions of the Pacific Oyster (Crassostrea gigas) into the North Sea. In detail, we combine ddRAD sequencing on the genomic level with RNAseq on the transcriptomic level to reveal outlier loci (SNPs) indicative of adaptation, as well as transcriptomic profiles from a translocation experiment to show immediate physiological reactions. Generally, we found low physical congruence between differentially regulated genes and outlier loci, indicating that different genes are involved on the different time scales. Functionally matching outlier loci and differentially expressed genes were however found for spliceosomal modification of mRNA and particularly for transposon activation, indicating that these variation creating processes are connected across eco-physiological and evolutionary time scales. By contrasting and identifying congruence between population outlier loci and population specific transcriptomic profiles, we can thus identify relevant processes acting during different phases of the invasive process. Together these will reveal a glimpse at the traits and processes characterizing the unique habitat specific mechanism underlying successful invasions.